2012
DOI: 10.1016/j.synthmet.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hollow poly(aniline-co-pyrrole)–Fe3O4 composite nanospheres and their microwave absorption behavior

Abstract: Hollow poly(aniline-co-pyrrole)-Fe 3 O 4 (HPAP-Fe 3 O 4 ) nanospheres with significant electromagnetic properties were successfully prepared via the oxidative polymerization of a mixture of aniline and pyrrole in the presence of a magnetic fluid, using a non-ionic surfactant as a template.The products were characterized by field emission scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray powder diffraction, thermogravimetric analysis and X-ray photoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…This plots showed some negative values at different portion which might be due to the noise [44]. Addition of Fe 3 O 4 particle may cause the hysteresis loss and eddy current loss which is responsible for magnetic loss [45]. Hence, the permittivity and permeability data supported the microwave absorption results of the prepared RAMs.…”
Section: 5mentioning
confidence: 56%
“…This plots showed some negative values at different portion which might be due to the noise [44]. Addition of Fe 3 O 4 particle may cause the hysteresis loss and eddy current loss which is responsible for magnetic loss [45]. Hence, the permittivity and permeability data supported the microwave absorption results of the prepared RAMs.…”
Section: 5mentioning
confidence: 56%
“…The reason is that the embedment of Fe 3 O 4 nanoclusters with low conductivity could reduce the effective doping of proton acid and destroy the conjugated structure of the PANI nanorod arrays, which results the decrease of conductivity and therefore the permittivity decreases [27]. In addition, e 00 exhibits a strong resonance peak at 14.3 GHz, which is maybe caused by the nature of the interface between the Fe 3 O 4 nanocluster and the PANI, and polarization by the Fe 3 O 4 nanocluster [28]. As for the complex permeability, the values for m 0 are all approaching to 1 and have no conspicuous difference with NG@PANI nanorod arrays (m 0 = 1),…”
Section: Resultsmentioning
confidence: 99%
“…Samples with low initial pH values show lower terahertz transmission intensity than the same with an initial pH value close to 9.13. It has been confirmed that the presence of conductive impurities such as: FeO or Fe 3 O 4 could not decrease the conductivity of dried powder [28,29]. However, FeO or Fe 3 O 4 impurities in samples A, B, C can be oxidized into Fe 2 O 3 eventually; the presence of Fe 2 O 3 impurity not only lowers the electrical conductivity of the electrodes, but also causes consumption of LiFePO 4 , as discussed above.…”
Section: Resultsmentioning
confidence: 75%